Organization, Control and the Single Entity Defense in Antitrust - Dean V. Williamson (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
Since at least the 1930's economists have puzzled over how to delineate the boundaries of the firm. With the advent of antitrust legislation in 1890, courts have been pressed to consider what constitute conspiracies between corporate entities to restrain commerce. By the 1940's, courts started to characterize conspiracies by sorting out what they are not — specifically, by extending the status of "single entity" to certain types of business arrangements. Both efforts in economics and in the law to sort out what constitutes a "firm" or "single entity" have focused on "control." A difficulty is that neither the law nor economics offer an operationally significant concept of control. Even so, both law and economics contribute concepts other than control that provide a way of understanding economic organization. These concepts — control rights, adaptation, delegation, and renegotiation — suggests how one can subsume the sometimes confusing array of single entity tests proposed in the case law within a two-stage sequence of tests.
Keywords: 330